MODEL PEMBELAJARAN ADAPTIF UNTUK MENINGKATKAN RASA PERCAYA DIRI DAN SOFT SKILL MAHASISWA - Dewi, Muthia; Dailami, Dailami (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: This study aims to analyze the effectiveness of the adaptive learning model in improving students' self-confidence and soft skills based on individual student abilities, using a qualitative approach with a multiple case study design that allows researchers to explore student perspectives, classroom interactions, and learning dynamics. The study involved students through observation, interviews, and documentation. The research subjects were 49 students of the education study program who attended lectures with the adaptive learning model. The instruments used were a self-confidence questionnaire, a soft skills assessment rubric, and classroom observations. The results of the study showed that student learning performance increased after the implementation of the adaptive learning model, such as students being able to express their confidence in their abilities in various situations and improving soft skills in the form of communication, teamwork, leadership, and problem-solving. Keywords: Adaptive Learning, Self-Confidence, Soft Skills Abstrak: Penelitian ini bertujuan untuk menganalisis efektivitas model pembelajaran adaptif dalam meningkatkan rasa percaya diri dan soft skill mahasiswa berbasis kemampuan individual mahasiswa, menggunakan pendekatan kualitatif dengan desain studi kasus ganda yang memungkinkan peneliti menggali perspektif mahasiswa, interaksi dalam kelas, serta dinamika pembelajaran. Penelitian melibatkan mahasiswa melalui observasi, wawancara, dokumentasi. Subjek penelitian adalah mahasiswa program studi pendidikan yang berjumlah 49 orang yang mengikuti perkuliahan dengan model pembelajaran adaptif. Instrumen yang digunakan berupa kuesioner kepercayaan diri, rubrik penilaian soft skill, serta observasi kelas. Hasil penelitian menunjukkan bahwa performa belajar mahasiswa meningkat setelah diterapkan model pembelajaran adaptif seperti mahasiswa mampu mengekspresikan kepercayaan dirinya pada kemampuan diri dalam berbagai situasi dan meningkatkan soft skill berupa komunikasi, kerja sama tim, kepemimpinan serta pemecahan masalah. Kata kunci: Pembelajaran Adaptif, Rasa Percaya Diri, Soft Skill